Distribution of Garlic Marketing Margin in West Miomaffo District, North Central Timor Regency, East Nusa Tenggara - Anggraeny Paridy; Stanis Man; Adrianus Ketmoen; Hironimus Dopo; Leni Marlina Kanadjo (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
Garlic farming is the livelihood of the community in Fatuneno village, North Central Timor Regency, East Nusa Tenggara Province, to meet the needs of children's life and education. The income of garlic farmers is the marketing margin obtained by garlic postharvest actors. The purpose of this study is to find out 1). How much is the marketing margin receipt of postharvest actors? 2). Is there a marketing margin distribution gap between garlic postharvest actors? This research method is a survey, and data collected randomly stratified; respondents consist of 46 farmers, eight collecting traders and three intermediary traders. Analysis tools used:1). To determine the marketing margin received by postharvest actors, the Marketing Margin equation is used. 2) For marketing margin distribution, use Gini Coefficient. There are three postharvest actors in garlic marketing distribution: producer farmers, collecting traders, and intermediary traders. In all three garlic marketing channel models, a short marketing channel benefits all three garlic postharvest actors. The distribution of marketing margins in the first and second marketing channels is at moderate evenness, and the third marketing channel is at high evenness.